2022
DOI: 10.3390/nano12234231
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Controlled Green Synthesis of Magnetic Nanoparticles Using Extracts of ‘Hairy’ Roots: Environmental Application and Toxicity Evaluation

Abstract: Magnetic nanoparticles (MNPs) were “green” synthesized from a FeCl3/FeSO4/CoCl2 mixture using ethanolic extracts of Artemisia tilesii Ledeb ‘hairy’ roots. The effect of chemical composition and reducing power of ethanolic extracts on the morphology, size destribution and other features of obtained MNPs was evaluated. Depending on the extract properties, nanosized magnetic materials of spherical (8–11 nm), nanorod-like (15–24 nm) and cubic (14–24 nm) shapes were obtained via self-assembly. Microspherical MNPs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Kobylinska et al green FeCl 3 /FeSO 4 /CoCl 2 mixture purified from the haiy root extract of Artemisia tilesii exhibited supermagnetic properties with no phyto-toxicities against Cichorium intybus and Lactuca sativa plants which are known for their distinguishably high and active seed germination rates. The seeds are thought to be more sensitive to metal toxicities and the study denotes that green oxide MNPs have no effect of germination rates of seeds suggesting their environmental safety [ 289 ].…”
Section: Future Perspective For Green Metal Nanoparticles In Biologic...mentioning
confidence: 99%
“…Kobylinska et al green FeCl 3 /FeSO 4 /CoCl 2 mixture purified from the haiy root extract of Artemisia tilesii exhibited supermagnetic properties with no phyto-toxicities against Cichorium intybus and Lactuca sativa plants which are known for their distinguishably high and active seed germination rates. The seeds are thought to be more sensitive to metal toxicities and the study denotes that green oxide MNPs have no effect of germination rates of seeds suggesting their environmental safety [ 289 ].…”
Section: Future Perspective For Green Metal Nanoparticles In Biologic...mentioning
confidence: 99%
“…Another study by Kobylinska et al investigated the use of ethanolic extracts of Artemisia tilesii Ledeb "hairy" roots to synthesize MNPs. 15 The findings revealed that this approach resulted in the production of MNPs with favorable magnetic properties that are minimally aggregated and well-dispersed in aqueous medium. Additionally, phytotoxicity analysis demonstrated that the biosynthesized MNPs had no inhibitory effect on two plant species, further highlighting their potential for environmentally friendly applications.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Moreover, these NPs can be used as efficient adsorbents in the treatment of water and wastewater. Another study by Kobylinska et al investigated the use of ethanolic extracts of Artemisia tilesii Ledeb “hairy” roots to synthesize MNPs . The findings revealed that this approach resulted in the production of MNPs with favorable magnetic properties that are minimally aggregated and well-dispersed in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…For example, magnetite NPs have been successfully synthesized using biomaterials such as Dolichos lablab extract, Musa acuminata peel ash, Cynara carduncculus leaf extract, Quince ( Cydonia oblonga Miller) seed extract, Aloe vera and Flaxseed extract, Kappaphycus alvarezii seaweed, the natural rubber latex of Hevea brasiliensis , lemon juice, Parkia speciosa Hassk. pod extract, the plant root extract of Chromolaena odorata , Artemisia tilesii L. “hairy” roots, Calotropis procera aqueous leaf extract, and Ficus Benghalensis plant leaf extracts [ 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. As already mentioned, plant substances can have multiple functions, so that no additional agents are needed.…”
Section: Introductionmentioning
confidence: 99%